The institutional performance of the Roxas City local government unit in Diwal conservation based on the localization mechanisms of Philippine Agenda 21 - Bernas, Mary Mayzee Dasal
The study sought to describe the institutional performance of the Roxas City Local Unit in Diwal conservation based on the localization mechanisms of Philippine Agenda 21. Specifically, it aimed to determined the following: (1) Roxas City LGU's employment of the localization mechanism of Philippine Agenda 21 in diwal conservation; (2) results of the peformance of the Roxas City LGU in the actual conservation of Diwal; and (3) constituency evaluation regarding the Diwal conservation policy., The objective were met through archival research and survey research with the protagonists like the Mayor, Vice Mayor, Sangguniang Panlungsod members, DA employees, and City Fisheries and Aquatic Resource Management Council members, and with the residents of Barangay Punta Cogon Roxas as respondents. It is found out that the protagonist generally have a positive attitude regarding the Diwal conservation efforts attributable to the nature of their jobs of Roxas City as the Seafood Capital of the Philippines, and to what kaase and Newton refer to as lifestyle/new politics. Statistcal and information facilities employed are found to be sufficient. At present, eight local legislations that have been formulated and implemented by the SP and CFARMC members are found to manifest the sustainable development of the Diwal. Moreover, there is an existing structure of multi-stakeholdership of the public authorities, DA employees, CFARMC members, and the Roxas City Diwal divers, which is consistent with the basic principle of the collective choices and responsibility towards the realization of sustainable development goals as espoused in PA 21. The operationalization strategies employed in Diwal conservation were found an ample amount of money has already been spent for the Diwal conservation efforts. Furthermore, it was also found out that there is a significant increase in the number of programs and trainings conducted from the year 2004 to 2005, manifesting a growing concern for the Diwal project. Development reports have been documented but were not communicated to larger institutions. Data shows that there is a remarkable revival in the Diwal industry. Constituency evaluation also shows that they are generally satisfied. The research findings showed that the Roxas City Local Government is effective in it substantial localization of the PA 21 concept of sustainable development applied in Diwal conservation. It was also to revive the Diwal stock, and was able to elicit positive reactions from its constituents. Thus comparative advantage, more legislations regarding the areas of tourism, export, quality of Diwal industry, and uphold the rights and welfare of the basic sectors which are the Diwal divers. In addition, strengthening of the basic sectors enhancing their leverage capabilities should also be pursued.